Development of hybrid microgrid model for frequency stabilization. Issue 5 (October 2017) - Veronica, A Jeya; Kumar, N Senthil
Power systems of today are highly complex and highly interconnected. It generates electricity by burning fossil fuels (coal, natural gas, diesel, nuclear fuel, etc.), which produces harmful gases and particles, pollutes environment, and degrades lives. To mitigate the bad impact of burning fossil fuels and meet the increase in electrical system, demand distributed energy sources employing nonconventional energy sources like wind and solar are used. Electric power generation through the nonconventional energy sources has become more viable and cheaper than the fossil fuel–based power plants. This article explores the development of a microgrid model incorporating wind turbine generators, diesel generator, fuel cells, aqua electrolyzers, and battery energy storage systems. An optimization scheme for fixing the proportional–integral controller parameters of frequency regulation is developed for different possible combinations of wind power with other distributed energy resources in the microgrid.